The effectiveness of playing Clay and Origami therapy to reduce anxiety pediatric patients hospitalized - Kodiriya, Nur Sofiatun; Munir, Zainal; Kholisotin, K; Fauzi, Ahmad Kholid; Wahid, Abdul Hamid (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Hospitality is a matter that requires the child to be hospitalized, which causes a lot of anxiety in children and for parents. Various feelings that often arise in children, namely anxiety, anger, sadness, fear and guilt. To reduce the effects of anxiety due to hospitalization experienced by children, we need a media that can express anxiety, one of which is play therapy. The purpose of this research was to determine the effect of clay and origami play therapy on reducing anxiety levels in hospitalization in preschool children (3-6 years) at Abdoer Rahem Situbondo Hospital. The design of this research uses Quasi Experiment Design, with the research design Time Series Design large sample of 90 preschool children (3-6 years), the sampling technique of this research uses purposive sampling, data collection is done using HARS observation sheets (hamilton anxiety Rating Scale) anxiety that is done directly to the respondent then measures the level of anxiety experienced by the respondent. This statistical test uses the Repeated Measures Anova test and the oneway anova test. The results of this research found there were differences in anxiety levels in preschoolers who were hospitalized before and after being given play therapy with a p-value of 0,000. While the comparative results of this research found that there was no difference in the level of anxiety reduction between the clay and origami play groups with a p-value of 0.977. Abstrak: Hospitalisasi hal yang mengharuskan anak dirawat dirumah sakit yang banyak mengakibatkan kecemasan pada anak maupun bagi orang tua, Berbagai perasaan yang sering muncul pada anak, yaitu cemas, marah, sedih, takut dan rasa bersalah. Untuk mengurangi dampak kecemasan akibat hospitalisasi yang dialami anak, diperlukan suatu media yang dapat mengungkapkan rasa cemasnya, salah satunya yaitu terapi bermain. Tujuan penelitian ini untuk mengetahui pengaruh terapi bermain clay dan origami terhadap penurunan tingkat kecemasan hospitalisasi pada anak usia prasekolah (3-6 tahun) di RSUD Abdoer Rahem Situbondo. Rancangan penelitian ini menggunakan Quasi Experiment Design, dengan desain penelitian Rancangan Rangkaian Waktu (Time Series Design) besar sampel 90 anak usia prasekolah (3-6 tahun), teknik pengambilan sampel penelitian ini menggunakan purposive sampling, Pengumpulan data dilakukan dengan menggunakan lembar observasi HARS(hamilton anxiety Rating  Scale ) kecemasan yang dilakukan langsung ke responden selanjutnya mengukur tingkat kecemasan yang dialami responden. Uji statistik ini menggunakan uji Repeated Measures Anova dan uji oneway anova. Hasil penelitian ini didapatkan ada perbedaan tingkat kecemasan pada anak usia prasekolah yang mengalami hospitalisasi sebelum dan sesudah diberi terapi bermain dengan p-value 0.000. Sedangkan Hasil perbandingan penelitian ini didapatkan bahwa tidak ada perbedaan tingkat penurunan kecemasan antara kelompok bermain clay dan origami dengan p-value 0.977.